2001
DOI: 10.1007/s001320050572
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approaches to osteochondral lesions of the talus

Abstract: Arthroscopic techniques still represent the treatment of choice in osteochondral lesions of the talus (OLT). Open techniques may be used as an alternative or may be complementary to arthroscopic treatments. They are especially indicated in cases of large osteochondral lesions, difficult localisations and in cases of recurrent interventions. In addition to the type of treatment for the lesion itself, the choice of an ideal surgical approach is of paramount importance. Indications, operative technique, possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
0
27
0
3
Order By: Relevance
“…Pseudarthroses as reported after medial malleolar osteotomy by several authors [4,9,11,[15][16][17] have obviously not been observed after refixation of the tibial bone block by Sammarco & Makwana and us.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Pseudarthroses as reported after medial malleolar osteotomy by several authors [4,9,11,[15][16][17] have obviously not been observed after refixation of the tibial bone block by Sammarco & Makwana and us.…”
Section: Resultsmentioning
confidence: 63%
“…Tibial wedge osteotomy · Osteochondritis dissecans · Osteochondral defect · Cartilage regeneration flexorum zu einer Subluxation oder einem Impingement der Sehnen mit entsprechend verzögerter oder unbefriedigender Rehabilitation, zu einer Dehnung des Gefäß-Nerven-Bündels oder einer Pseudarthrose, aber auch zu Inkongruenzen im Gelenkbereich mit nachfolgender Arthrose führen [4,9,11,[15][16][17] ation or impingement of the tendons interfering with rehabilitation, stretching of the neurovascular bundle and nonunion but also to incongruity of the articular surface with subsequent osteoarthritis [4,9,11,[15][16][17]. For these reasons a new approach has been developed without involving the malleoli: the temporary removal of a bone block from the weight-bearing anterior part of the distal tibia.…”
Section: Introductionunclassified
“…Arthroscopically guided drillings are limited to those lesion that could be arthroscopically identified [60]. In the remaining cases, open procedures are justified [57]. Based on these principles, CT-based computer assisted surgery (CAS) guided retrograde drilling of osteochondral lesions has been described with promising results as a new technique [19,52].…”
Section: Computer Assisted Surgery (Cas) N Ct-based Casmentioning
confidence: 99%
“…Eine weitere Option ist die röntgenbildverstärker-gestützte retrograde Anbohrung, die aber aufgrund der schlechten Visualisierung wenig Erfolg versprechend ist [15]. Daher sehen einige Autoren auch die Indikation für ein offenes Vorgehen [19]. Dafür ist aber häufig ein ausgedehnter Zugang mit Osteotomie nötig [19].…”
Section: Navigierte Retrograde Anbohrung Bei Osteochondrosis Dissecanunclassified
“…Daher sehen einige Autoren auch die Indikation für ein offenes Vorgehen [19]. Dafür ist aber häufig ein ausgedehnter Zugang mit Osteotomie nötig [19]. Zur genaueren und weniger schädigenden retrograden Bohrung wurde die Computertomographie (CT)-basierte computerassistierte Chirurgie (CAS)-gesteuerte Technik beschrieben [2,7,10,18].…”
Section: Navigierte Retrograde Anbohrung Bei Osteochondrosis Dissecanunclassified